2011
DOI: 10.5021/ad.2011.23.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Panniculitis Associated with Acinar Cell Carcinoma of the Pancreas: A Case Report

Abstract: Pancreatic panniculitis is a rare type of disorder associated with pancreatic diseases. We describe here a case of 54-year-old man who was admitted to the Department of Dermatology with the diagnosis of erythema nodosum. The patient presented with a 9-month history of painful erythematous nodules on the extremities, joint pain and swelling, and weight loss. A highly elevated level of pancreatic lipase was found on the laboratory examinations. The biopsy specimens from the skin lesions showed subcutaneous fat n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…2 In addition to our case, we identified in the English literature 30 well-documented cases of complete PPP syndrome associated with pancreatic carcinoma. 16,[20][21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][37][38] These patients were mostly elderly men (87%) with a mean age at diagnosis of 61.2 ± 13 years (range, 20-88 years). Acinar cell carcinoma, in 58% of the cases, was the most common pancreatic neoplasm, whereas metastatic disease was documented in 21 patients.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In addition to our case, we identified in the English literature 30 well-documented cases of complete PPP syndrome associated with pancreatic carcinoma. 16,[20][21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][37][38] These patients were mostly elderly men (87%) with a mean age at diagnosis of 61.2 ± 13 years (range, 20-88 years). Acinar cell carcinoma, in 58% of the cases, was the most common pancreatic neoplasm, whereas metastatic disease was documented in 21 patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In cases associated with acute or chronic pancreatitis, the mortality rate was as high as 24%, 2 and when associated with pancreatic carcinoma, it was nearly 74%. [20][21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][37][38] Subcutaneous nodules may be the presenting symptom of an otherwise occult pancreatic disease. In fact, Hughes et al 17 reported that panniculitis was the presenting symptom in 65% of patients with pancreatic carcinoma.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaundice is an infrequent finding (12%) and complications related to lipase release (panniculitis) are common. 2 Abdominal pain is reported to be present in 32% and nausea and vomiting in 23% of patients. 3 To the best of our knowledge, this is the first described case of spontaneous rupture of ACC that presented as an acute abdomen.…”
Section: Introductionmentioning
confidence: 98%
“…Pancreatic panniculitis rarely (2-3%) accompanies pancreatic disease; therefore, diagnosing the disease can sometimes be difficult (2). Physicians should include pancreatic panniculitis in the differential diagnosis of erythema nodosum.…”
mentioning
confidence: 99%